2016
DOI: 10.1038/srep21807
|View full text |Cite
|
Sign up to set email alerts
|

Long-term High Fat Ketogenic Diet Promotes Renal Tumor Growth in a Rat Model of Tuberous Sclerosis

Abstract: Nutritional imbalance underlies many disease processes but can be very beneficial in certain cases; for instance, the antiepileptic action of a high fat and low carbohydrate ketogenic diet. Besides this therapeutic feature it is not clear how this abundant fat supply may affect homeostasis, leading to side effects. A ketogenic diet is used as anti-seizure therapy i.a. in tuberous sclerosis patients, but its impact on concomitant tumor growth is not known. To examine this we have evaluated the growth of renal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 60 publications
0
33
0
1
Order By: Relevance
“…While epidemiological associations among obesity, cancer, and ketogenic diets are debated (Liskiewicz et al, 2016; Wright and Simone, 2016), a meta-analysis using ketogenic diets in animal models and in human studies suggested a salutary impact on survival, with benefits prospectively linked to the magnitude of ketosis, time of diet initiation, and tumor location (Klement et al, 2016; Woolf et al, 2016). Treatment of pancreatic cancer cells with ketone bodies ( d -βOHB or AcAc) inhibited growth, proliferation and glycolysis, and a ketogenic diet (81% kcal fat, 18% protein, 1% carbohydrate) reduced in vivo tumor weight, glycemia, and increased muscle and body weight in animals with implanted cancer (Shukla et al, 2014).…”
Section: Ketone Bodies In Cancer Biologymentioning
confidence: 99%
“…While epidemiological associations among obesity, cancer, and ketogenic diets are debated (Liskiewicz et al, 2016; Wright and Simone, 2016), a meta-analysis using ketogenic diets in animal models and in human studies suggested a salutary impact on survival, with benefits prospectively linked to the magnitude of ketosis, time of diet initiation, and tumor location (Klement et al, 2016; Woolf et al, 2016). Treatment of pancreatic cancer cells with ketone bodies ( d -βOHB or AcAc) inhibited growth, proliferation and glycolysis, and a ketogenic diet (81% kcal fat, 18% protein, 1% carbohydrate) reduced in vivo tumor weight, glycemia, and increased muscle and body weight in animals with implanted cancer (Shukla et al, 2014).…”
Section: Ketone Bodies In Cancer Biologymentioning
confidence: 99%
“…In total, 72% (21/29) of the animal studies provided evidence for anti-tumor effects of the KD, while in only one study evidence for pro-tumor effects was found. Noteworthy, this study [64] provided evidence for both anti-and pro-tumor effects, depending on the length of the KD feeding period. The two meta-analyses concluded that there is overall evidence for anti-tumor effects of KDs in mice [70,71].…”
Section: Resultsmentioning
confidence: 63%
“…A second aspect to the role of lipids in promoting cancer is the influence of exogenous sources of lipids in facilitating tumorigenesis and metastasis. Numerous studies have experimented with high lipid content diets using mouse models and reported increases in tumour growth and/or metastasis, implicating high fat ketogenic diets [34][35][36] or specific lipids such as cholesterol [37] or palmitic acid [38] in promoting cancer. There is a variety of mechanisms by which high concentrations of dietary lipids can exert a tumorigenic effect.…”
Section: Lipids As Promoters Of Cancermentioning
confidence: 99%
“…There is a variety of mechanisms by which high concentrations of dietary lipids can exert a tumorigenic effect. According to Liśkiewicz and colleagues, their high fat ketogenic diet administered ad libitum to mice led to activation of ERK1/2 which controls cell proliferation, differentiation and survival [39], as well as elevated mTOR signalling in renal tumours [34]. In a different study, high fat diets caused acetoacetate levels in the serum of recipient mice to increase, subsequently leading to enhanced tumour growth of xenograft human melanoma cells with a V600E mutation in the BRAF gene [35].…”
Section: Lipids As Promoters Of Cancermentioning
confidence: 99%